Design and development of wireless sensor network architecture for smart farm - Cagatan, Gerard Kevin B. (Animo Repository, 2020)
A system and method for designing and developing a wireless sensor network for measuring the environmental parameters of a smart farm comprising: deploying a plurality of sensor nodes and a central node in predefined locations in a smart farm; initializing each sensor nodes’ connection with the central node; acquiring a plurality of sensor data in each node at specific time intervals set by the user; sending control signals to actuators if the sensor data exceeds a predefined threshold value; transmitting the acquired sensor data into the central node via a wireless communications module; storing the received sensor data in the central node; and displaying the saved sensor data in the central node’s graphical user interface.